Expression and purification of myristoylated matrix protein of Mason-Pfizer monkey virus for NMR and MS measurements - Prchal, Jan (2011)
Matrix proteins play multiple roles both in early and late stages of the viral replication cycle. Their N-terminal myristoylation is important for interaction with the host cell membrane during virus budding. We used Escherichia coli, carrying N-myristoyltransferase gene, for the expression of the myristoylated His-tagged matrix protein of Mason-Pfizer monkey virus. An efficient, single-step purification procedure eliminating all contaminating proteins including, importantly, the non-myristoylated matrix protein was designed. The comparison of NMR spectra of matrix protein with its myristoylated form revealed substantial structural changes induced by this fatty acid modification.